Recent advances in responsive liquid crystal elastomer‐contained fibrous composites - Zhibo Zhang; Jiajun Li; Ruicong Zhang; Ruirun Chen; Yumin Zhang; Tianyu Wang; Kun‐Lin Yang; Jiaqi Zhu (Responsive Materials)
Abstract Responsive polymers can react to surrounding environments by changing their physical and/or chemical properties. Among them, liquid crystal elastomers (LCEs) have emerged as one of the important branches in the field of applied polymer science due to their significant advantages in flexible mechanics and shape memory. Manufacturing LCE fibers with a large specific surface area and functional fillers has become a research hotspot in recent years. This type of LCE‐contained fibrous composite (LCEF) exhibits not only extremely high response sensitivity but also excellent axial mechanical strength and a high degree of deformation freedom. In this paper, we provide a bird's eye view of recent developments in LCEF, including structural designs, synthesis and forming methods, mechanical response principles and modes. Furthermore, we discuss recent advances of LCEF in artificial muscles, smart textiles, biomimetic systems, intelligent soft machines, followed by challenges and possible routes in fabrications and applications of LCEF. At the end, we aim to provide a perspective for an emerging field of stimulus‐responsive polymeric fiber composites.